The transformations experienced by the subjects of EJA-EPT (PROEJA FIC) (Revista Contexto & Educação, 2025)
In 2009, YAE-PTE, which combines elementary education with Initial and Continuing Education (ICE), began to be encouraged and promoted. Despite the conflicting movements of support and silence that have characterized the historical development of YAE-PTE, the significant provision of this educational policy was observed in the technical cooperation agreement between the Federal Institute Farroupilha), campus Júlio de Castilhos), and the Municipal Education Network of Tupanciretã. In this context, the objective is to identify the transformations experienced by students who have accessed the YAE-PTE (PROEJA ICE) policy in the municipality of Tupanciretã. This research is characterized as exploratory and descriptive, and the data collection methods include questionnaires for students, interviews with administrators, field diaries, and dialogue groups. Content analysis was used for the analysis. The conclusion is that the transformations experienced by students are numerous, and in the researched reality, they include changes in the surrounding environment. Experiences and challenges are constant in this journey, and it is through these experiences and the pedagogical work developed that the policy, as well as the access, retention, and success of the students, are strengthened.
Keywords: Youth and Adult Education; Professional and Technological Education; Public policies